Síntese e caracterização de compostos de coordenação a base de estanho e estudos em catálise - Brainer, Nívea dos Santos (2020)
In the last few decades, interest in heterogeneous catalytic systems has been increasing, mainly due to the capacity for separation, regeneration and reuse, making the process more efficient and sustainable. Metal organic frameworks (metal organic frameworks -MOFs) and their derivatives are promising heterogeneous catalysts, as they exhibit high surface area, well- defined pore structure and structural versatility. In this sense, this work aims at the simple and mild synthesis via ultrasonic method at room temperature of zinc MOFs (ZIF-8) doped with tin (1, 10 and 15%), Sn-MOFs with different sources of tin (SnCl4 and SnSO4) and SnO2 derived from Sn-MOFs, for application as heterogeneous catalysts in ethyl acetate transesterification reactions and propionic acid esterification. The MOFs were characterized by powder X-ray diffraction (XRD), spectroscopy in the region of the medium infrared by Fourier transform (FTIR), nitrogen physisection, thermogravimetric analysis (TGA), scanning electron microscopy (SEM) and spectrometry of X-ray dispersive energy (EDX). The XRD results for Sn-MOFs prepared with SnSO4 showed that they are isostructural to other Sn-MOFs reported in the literature, however in this work a milder method was used. On the other hand, for Sn-MOFs obtained with the use of SnCl4 in different concentrations (Sn-MOF-U0.125M and Sn-MOF-U0.25M), no significant structural difference was observed. SnO2 showed structural purity and surface area superior to some works reported in the literature. ZIF-8 doped with 1, 10 and 15% of tin exhibited similar crystalline structures compatible with the simulated pattern of ZIF-8, and distinct morphologies in face of the increase in Sn in the structure of ZIF-8. The previous results obtained for the ethyl acetate transesterification reaction demonstrated that ZIF-8 and its derivatives incorporated with tin led to greater conversions of ethyl acetate, of about 25% in 4 hours at 120 oC, in relation to the Sn-MOFs and SnO2, which did not show significant conversion results. As for the esterification reactions, Sn-MOFs proved to be more efficient, in which Sn-MOF-U0.25M showed a conversion of propionic acid of approximately 55% in two hours of reaction. Finally, the results showed that the use of these materials as heterogeneous catalysts in the studied reactions is promising. In addition, this work opens doors for the insertion of new materials based on tin in the area of heterogeneous catalysis.